The license agreement: a flexible tool for technology transfer (2020)
This research book aims to analyze technology transfer contracts in two directions: first, in a general framework that assesses the characteristics of the globalized trade scenario and, second, from the in-depth review of the contract of license. This study justifies recognizing that technology is the engine of development and not a mere generator of wealth, so it is essential to measure its impact and transformative force in society. Reviewing the relationship between technology as a source of transformation, the market as a space for international traffic in intangible goods and the law asa regulatory framework is necessary to interpret how this context permeates business relationships over intangible goods. The development of the themes is divided into two main parts. The first, The Intangible Goods Market, addresses aspects related to competition law and intellectual property and introduces the subject of contracts.The second part, The license agreement for the transfer of intangible goods, explains in detail the figure of the “license agreement”, to finally close with the registration of technology transfer contracts imported to Colombia. Among the findings, contracts have become more flexible and open to allow for self-regulation and the use of a wide variety of atypical figures, and thus make possible the circulation of intangibles in aglobalized world. From this, it is concluded that in the processes of construction of the agreements when negotiating their execution, not only the inter-party interests must be valued, but also the influence of new regulators, territorial areas of free competition and a variety of aspects that make the realization of contract craftwork.